Dietary Folic Acid Alters Metabolism of Multiple Vitamins in a CerS6- and Sex-Dependent Manner - Barron, Keri; Ogretmen, Besim; Krupenko, Natalia (Frontiers in Nutrition, 2021)
Folic Acid (FA), an oxidized synthetic pro-vitamin B9, is widely used in vitamin supplement formulations and food fortification to maintain optimal folate status in humans. Studies on FA efficiency in improving folate status and correcting folate deficiency pathologies are abundant, but precise knowledge of FA effects on human and animal tissues is not available. In our recent study, ten-week-old wild-type and CerS6 knock-out (KO) mice were placed on FA-deficient, control, or FA over-supplemented diets for 4 weeks. Untargeted metabolomics characterization of mouse liver, brain and testes tissues after the dietary treatment revealed profound effects of the FA on liver metabolome. Here we present the analysis of dietary FA effects on tissue concentrations of other vitamins in mice. Despite the expectation that identical dietary supply of the vitamins (excluding FA) to each group should support similar tissue vitamins concentrations, metabolomic data demonstrate significant alterations of tissue concentrations of multiple vitamins by different levels of FA supplementation that were sex- and genotype-dependent. Moreover, we found significant differences in liver concentration of retinol, thiamin diphosphate, pantetheine, pyridoxal and pyridoxamine between males and females. While liver had more changes in vitamins and vitamin derivative levels, the brain tissue and testes also showed changes linked to FA supplementation. Over-supplementation with FA had negative effects on concentrations of vitamins A, B1, B2 and B6, or their metabolites in the liver, but increased intermediates in CoA biosynthesis, as well as gamma/beta-tocopherol and phosphorylated forms of B6 in the CerS6 KO brain. Overall, our data demonstrate that dietary FA supplementation significantly affects metabolism of other vitamins, and these effects depend on CerS6 status and sex of the animal. Further research is required to determine whether the observed effects are specific to FA, and what are the mechanisms involved.